3D objects creation approaches - Vorontsova, Darya; Dashkevych, Andrii; Fedchenko, Hanna; Tiahlo, Vladislav (Khmelnytskyi national university, 2021)
In this paper are discussed the application of 3D technologies, which are reflected in various areas of life, such as education, science, engineering and entertainment industry. The use of 3D technology in the educational process can significantly increase its efficiency by bringing the virtual computer environment closer to the real three-dimensional world. But for now the use of augmented reality in teaching is only gaining momentum. Many applications are still quite primitive, but developers are actively working on their refinement, increasing the amount of educational content, improving quality. It is not entirely clear what the basic steps of 3D modeling are for importing a model into augmented reality. Today there are a large number of areas of application of 3D models. The question is whether it is possible to use a single algorithm for all models and which. The aim of this work is to increase the level of use of 3D technologies in the educational process for an effective and external interactive way of providing information. In the course of the work the methods of creating 3D content for different areas of application such as game industry, 3D visualization, 3D printing, AR projects, holographic fans, preliminary assessment of technical properties of the product and etc were considered. Data analysis has been shown that for each area of application 3d contenthas its own requirements and features. This information was identified and presented in the form of a comparative table. Based on the analysis of modern methods of developing 3D content for different applications, it was proposed to combine the requirements for creating 3D models of individual areas. Based on the proposed combination, a small experiment was performed. 3D model of the character for the children audio-encyclopedic stories educational application was designed. The obtained models were also integrated in the augmented reality environment. After analyzing the relevant indicators, we concluded that the requirements for 3D content in these areas are the same. The paper also structured the main stages for creating 3D models of different applications, which in turn brings clarity and clarity to the process of developing 3D content for further import into AR training projects.

В даній статті розглядається питання застосування 3D-технологій, які знаходять своє відображення в різноманітних сферах життєдіяльності, наприклад таких як: освіта, наука, техніка та індустрія розваг. Використання 3D технологій в освітньому процесі дозволяє суттєво підвищити його ефективність завдяки наближенню віртуального комп’ютерного середовища до реального тривимірного світу. Але, поки що використання доповненої реальності в навчанні тільки набирає обертів. Багато додатків залишаються досить примітивними, але розробники активно працюють над їх доопрацюванням, збільшенням кількості освітнього контенту, підвищенням якості. Актуальною постає задача швидкого та якісного алгоритму створення 3D контенту для подальшого імпорту його у AR навчальні проекти. Не зовсім зрозуміло, які основні етапи3D моделювання необхідні для імпорту моделі у доповнену реальність. Сьогодні існує велика кількість сфер застосування 3D моделей. Виникає питання чи можна використовувати один єдиний алгоритм для усіх моделей та який. Метою роботи є підвищення рівня використання 3D технологій в освітньому процесі для ефективного і наочного інтерактивного способу подачі інформації. В ході роботи були розглянуті методики створення 3D контенту для деяких розпоширених сфер застосування таких як: ігрова індустрія, 3D візуалізація, 3D друк, AR проекти, голографічні вентилятори, попередня оцінка технічних властивостей виробу та ін. Аналіз даних показав, що для кожної сфери застосування 3D контент має свої вимоги та особливості. Зазначена інформація представлена в статті у вигляді порівняльної таблиці. На основі аналізу сучасних методів розробки 3D контенту для різних сфер застосування було запропоновано об'єднати вимоги до створення 3D моделей окремих сфер. Спираючись на запропоноване поєднання був проведений невеликий експеримент. Було створено 3D модель персонажу освітнього додатку аудіо енциклопедичних історій для дітей. Також було здійснено інтегрування отриманої моделі в середовище доповненої реальності. Проаналізувавши відповідні показники прийшли до висновку, що вимоги для 3D контенту зазначених сфер однакові. В роботі також структуризували основні етапи для створення 3D моделей різних сфер застосування, що в свою чергу вносить ясність та чіткість в процес розробки 3D контенту для подальшого імпорту його у AR навчальні проекти.
Підхід щодо створення 3D-об'єктів для імпорту їх у AR проекти
Keywords: 3D model; AR projects; 3D technologies; educational process; augmented reality; 3D модель; AR проекти; 3D технології; освітній процес; доповнена реальність